Use of a cyclo-P4 building block – a way to networks of host–guest assemblies. Issue 34 (25th August 2020) - Peresypkina, Eugenia; Bielmeier, Martin; Virovets, Alexander; Scheer, Manfred
Abstract : A one-pot self-assembly template-controlled reaction is reported to result in a 2D coordination network of first host-guest assemblies P3 Se4 @[{(Cp′′Ta(CO)2 (η 4 -P4 ))Ag}8 ] 8+ of 2.49 nm in size based on an organometallic complex with a cyclo -P4 end-deck. Abstract : Despite the proven ability to form supramolecular assemblies via coordination to copper halides, organometallic building blocks based on four-membered cyclo -P4 ligands find only very rare application in supramolecular chemistry. To date, only three types of supramolecular aggregates were obtained based on the polyphosphorus end-deck complexes Cp R Ta(CO)2 (η 4 -P4 ) (1a : Cp R = Cp′′; 1b : Cp R = Cp′′′), with none of them, however, possessing a guest-accessible void. To achieve this target, the use of silver salts of the weakly coordinating anion SbF6 − was investigated as to their self-assembly in the absence and in the presence of the template molecule P3 Se4 . The two-component self-assembly of the building block 1a and the coinage-metal salt AgSbF6 leads to the formation of 1D or 3D coordination polymers. However, when the template-driven self-assembly was attempted in the presence of an aliphatic dinitrile, the unprecedented barrel-like supramolecular host–guest assembly P3 Se4 @[{(Cp′′Ta(CO)2 (η 4 -P4 ))Ag}8 ] 8+ of 2.49 nm in size was formed. Moreover, cyclo -P4 -based supramolecules are connected in a 2D coordination network by dinitrile linkers. The obtained compounds were characterised by mass-spectrometry, 1 H and 31 P NMR spectroscopy and X-ray structure analysis.